Context matters: emotional responses to urban greening interventions depend on city setting - Freya M. Thomas; Luke Greenacre; Georgia E. Garrard; Richard A. Fuller; Adrian G. Dyer; Ascelin Gordon; Christopher D. Ives; Lee Harrison; Rodney Van der Ree; Sacha Jellinek; Jacinta E. Humphrey; Sarah A. Bekessy (Urban Ecosystems, 2026)
Urban green spaces deliver a remarkable range of human health and well-being benefits, and there is substantial, global effort into incorporating urban greening into the design of cities. However, intense competition for space in cities means small interstitial gaps in the urban fabric are being used for many contemporary green spaces, such as planter boxes or raised garden beds. These small urban greening interventions have become increasingly popular in recent years, especially following the COVID-19 pandemic when access to nature in cities became a key public concern. It is not yet known whether planter boxes in urbanised settings can provide well-being benefits as traditional parks and reserves have been found to. Here we show, using manipulated images, that as much as a 60% difference in a participant’s ( n = 1200) emotional response to a planter box green space is due to changes in city context. This indicates that small green spaces in cities may provide quite different well-being benefits depending on their specific urban setting. As planting context is more important than the focal details of small green space interventions for creating emotional responses in urban residents, city planning could strategically consider not just whether , but where to integrate nature into urban areas to maximise well-being outcomes for residents.